Pemanfaatan Limbah Cangkang Kerang dan Abu Jerami Sebagai Substitusi Parsial Terhadap Kuat Tekan Beton - Petrus Tomu Natal Marpaung; LOLOM EVALITA HUTABARAT; Setiyadi Setiyadi (LPPM, 2023)
As an archipelagic country and agricultural land, coastal areas and agriculture dominate most of Indonesia's mainland. These conditions make oyster shells waste and rice husk ash very easy to obtain in large quantities as a component for making concrete. It can be an appropriate technological solution for manufacturing concrete with local wisdom. The research used 24 specimens in cylinders with a diameter of 15cm and a height of 30cm, referring to SNI 7656-2012 with a k-300 or 25 MPa concrete plan. The composition of 10% oyster-shells waste was used as a substitute for fine aggregate, while the composition of rice husk ash varied, namely 3%, 5%, and 7% as a substitute for cement. Concrete curing was carried out 14 and 28 days before the compression test. The compressive strength test results for regular concrete at 14 and 28 days, respectively, were 24.72 MPa and 25.00 MPa according to the design compressive strength. The compressive strength value of concrete with a mixture of rice straw ash and shellfish increased from regular concrete at 14 days of age, namely 25.95 MPa, 27.18 MPa, and 26.04 MPa for each variation of 3%, 5%, and 7 %. Whereas at 28 days of concrete age, using variations of shellfish waste mixture of 3%, 5%, and 7% obtained compressive strength of 27.18 MPa, 28.21 MPa, and 26.99 MPa. Thus, there is an increase in compressive strength ranging from 0.05% -0.12% in concrete using a mixture of oyster-shells waste and rice husk ash